Temperature dependences of interface reactions and Tb diffusion behavior of Pr-Tb-Cu-Al alloys/Nd-Fe-B magnet. (15th January 2021) - Lu, Kechao; Bao, Xiaoqian; Song, Xinfang; Wang, Yanxin; Tang, Minghui; Li, Jiheng; Gao, Xuexu
Abstract: Interface reactions and structure of Pr52.5 Tb17.5 Cu30, Pr60 Tb20 Al20 and Pr60 Tb10 Cu15 Al15 (at%) alloys with Nd-Fe-B magnets processed at various temperatures were systematically investigated. The alloys first melted and diffused through grain boundaries, and a higher temperature was required to form Tb-rich shells. Compared to Pr52.5 Tb17.5 Cu30 and Pr60 Tb20 Al20, Pr60 Tb10 Cu15 Al15 with Al/Cu co-doping promoted Tb diffusion through grain boundaries especially at a lower temperature than 800 °C, and consequently developed continuous and thin Tb-rich grain boundaries. We presented two-step diffusion process with Pr60 Tb10 Cu15 Al15, including low-temperature diffusion to accelerate Tb diffusion through grain boundaries and subsequent high-temperature diffusion to mainly promote Tb grain diffusion. Consequently, due to more homogeneous Tb distribution and resulting thinner Tb-rich grain boundaries, coercivity increment of 11 kOe was achieved by introducing only 0.33 wt% Tb, obviously lower than 0.48 wt% in conventional one-step diffusion magnet. Graphical abstract: Image, graphical abstract